High performance wireless Ethernet. - Heegard, C. (IEEE Communications magazine)
This article considers the IEEE 802.11b standard for high-performance wireless Ethernet and a proposed extension that provides for 22 Mb/s transmission. The IEEE 802.11 sets standards for wireless Ethernet or wireless local area networks. The article describes the history of the IEEE 802.11 standards and the market opportunities in the wireless Ethernet field. The article gives a brief description of the media access control layer and then presents details about the physical layer methods, including coding descriptions and performance evaluations. The article also discusses the role and limitations of spread spectrum communications in wireless Ethernet